2016
DOI: 10.1021/acs.jafc.6b02199
|View full text |Cite
|
Sign up to set email alerts
|

Aspergillus flavus SUMO Contributes to Fungal Virulence and Toxin Attributes

Abstract: Small ubiquitin-like modifiers (SUMOs) can be reversibly attached to target proteins in a process known as SUMOylation, and this process influences several important eukaryotic cell events. However, little is known regarding SUMO or SUMOylation in Aspergillus flavus. Here, we identified a novel member of the SUMO family in A. flavus, AfSumO, and validated the existence of SUMOylation in this pathogenic filamentous fungus. We investigated the roles of AfsumO in A. flavus by determining the effects of AfsumO mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
73
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(79 citation statements)
references
References 50 publications
6
73
0
Order By: Relevance
“…Like the other mutants of SUMOylation components in other organisms (Gujjula et al ., ; Leach et al ., ; Nie et al ., ; Wong et al ., ), Δ Mosmt3 , Δ Moaos1 , Δ Mouba2 , Δ Moaos1 Δ Mouba2 and Δ Moubc9 showed significantly reduced mycelial growth, conidiation, conidial germination, appressorium formation, stress resistance and pathogenicity. Deletion of the SUMOylation‐associated genes was not lethal, unlike in S. cerevisiae and C. glabrata (Gujjula et al ., ; Schwarz et al ., ), but deletion of even one of these genes almost abolished SUMOylation in M. oryzae .…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Like the other mutants of SUMOylation components in other organisms (Gujjula et al ., ; Leach et al ., ; Nie et al ., ; Wong et al ., ), Δ Mosmt3 , Δ Moaos1 , Δ Mouba2 , Δ Moaos1 Δ Mouba2 and Δ Moubc9 showed significantly reduced mycelial growth, conidiation, conidial germination, appressorium formation, stress resistance and pathogenicity. Deletion of the SUMOylation‐associated genes was not lethal, unlike in S. cerevisiae and C. glabrata (Gujjula et al ., ; Schwarz et al ., ), but deletion of even one of these genes almost abolished SUMOylation in M. oryzae .…”
Section: Discussionmentioning
confidence: 98%
“…Subsequent identification of SUMOylated motifs in conidiation‐related genes further supports the hypothesis that the modification of conidiation‐related genes by SUMO controls conidiation in M. oryzae . Similar conidiation phenotypes were reported in SUMOylation mutants of A. nidulans and A. flavus (Nie et al ., ; Wong et al ., ). These results suggest that SUMOylation is crucial for conidiation in filamentous fungi.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In A. flavus , Lan found that histone acetyltransferase and deacetylase play important roles in the production of aflatoxin by regulating modifications of histone acetylation (Lan et al ., ; Lan et al ., ). In addition, the results of acetylation‐mediated aflatoxin biosynthesis agree with the results of other reported PTMs in A. flavus , including phosphorylation (Ren et al ., ), SUMOylation (Nie et al ., ) and succinylation (Ren et al ., ). Taken together, we conclude that lysine acetylation is critical for secondary metabolism in A. flavus .…”
Section: Discussionmentioning
confidence: 99%
“…And then, an electron microscope (Leica, Wetzlar, Germany) was used to observe the morphology of conidiophores. For sclerotial production assay, each strain was spotted onto WKM agar medium and grown at 37°C for corresponding days in darkness (Nie et al ., ). Then, the plates were sprayed with 75% ethanol to wash mycelial and conidia so as to expose sclerotial.…”
Section: Methodsmentioning
confidence: 97%